Dampak Teknik dan Metode Penerjemahan terhadap Makna Pragmatik: Tindak Tutur Asertif dalam Terjemahan Minna no Nihongo 2 dan ChatGPT - Bulqois, Ifana; Aryanto, Bayu (KIRYOKU, 2026)
The growing use of ChatGPT in Japanese translation highlights the need to evaluate the quality of its output in comparison with human-produced translations. This study examines how differences in translation techniques, as defined by Molina and Albir (2002), and translation methods proposed by Newmark (1988), influence pragmatic meaning and illocutionary functions in assertive speech acts. The data consist of conversational texts from Minna no Nihongo 2, which were analyzed using a qualitative descriptive approach based on the applied techniques, methods, and assertive categories. The findings show that the original textbook translation tends to employ semantic translation supported by amplification and modulation, whereas ChatGPT more frequently produces communicative translation through reduction and adaptation. The study concludes that although ChatGPT can generate clear and communicative translations, it does not consistently preserve the pragmatic nuances and politeness features characteristic of Japanese.